Providing distance learning support for the present & future open distance learning environment what do the learners say? A case study of Universiti Utara Malaysia - Dzakiria, Hisham (2004)
This qualitative study reports in some detail the experience of a small group of distance learners as they progress through their courses at Universiti Utara Malaysia (UUM). An initial literature review suggested that while a number of studies had been completed in the past two decades that report student characteristics, motivations, and prior experiences of study, most of these studies had been carried out from the point of view and perspective of the providing institutions, not from the perspective of students.This paper looks at distance learning as described by the learners- it is their story, their experience, and their perspective.In particular, this paper looks at learning support in distance learning at UUM, an issue that arose from discussions with the students, rather than being preordained by the research design or derived directly from my own initial interest as a distance educator and as a researcher. From these findings conclusions have been drawn regarding the role of learning support and guidelines to improve future learning support services to facilitate and provide a better ODE educational experience and outcome in Malaysia.